Kontribusi Mahasiswa Magang dalam aktivasi Co- Learning Space untuk peningkatan UMK di OK OCE Indonesia - Amanda Berliana Putri; Arton Briyan Prasetio; Stella Stella; Satriyo Wibowo (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2022)
This Internship Final Report was written to explain how the writer’s activities during her Internship in OK OCE Indonesia through Magang Bersama Kampus Merdeka which was held by the Ministry of Education, Culture, Research and Technology of the Republic Indonesia, OK OCE is a social movement in job creation through the entreprenurial movement. In this Report, In this Report, it will be explained how the writer’s daily life as a part of the 3rd batch of apprentice participants OK OCE Indonesia in the research and learning divison in the Project “Activation of Co-Learning Space to Improve Competence and Competitiveness of MSEs”. As for this Report, it will be explained how the writer’s supports MSMEs in Indonesia in efforts to digitalize businesses by referring to the seven OK OCE curriculum standards.